Relationship between RBC parameters, HBA₂ level and molecular findings in Alpha Thalassemia: HTAR experience / Ahmad Izzat Ahmad Basri - Ahmad Basri, Ahmad Izzat (2016)
Alpha thalassemia is a common recessively inherited blood disorder due to mutation or deletion of one or more alpha globin gene. Nowadays, the initial step for screening of alpha thalassemia is by determining the MCV and MCH values. Further investigation includes Hb analysis and confirmation test by molecular analysis. Among the popular molecular method commonly used today is the polymerase chain reaction (PCR). HTAR usually outsource its molecular tests for alpha thalassemia. However, only about 50% of the outsourced samples were positive for alpha thalassemia. Thus, to avoid performing molecular analysis unnecessarily, this study was proposed to find if there is any relationship between the RBC parameters, HBA₂ level and molecular findings for better screening of patients prior to request for molecular analysis. A total of 197 data which consisted of RBC parameters (TRBC, Hb, RDW, MCV, MCH, MCHC and Retic Count), HBA₂ level and molecular findings from HTAR patients diagnosed with alpha thalassemia in 2014. Independent t-test was conducted to evaluate whether the RBC parameters and , HBA₂ level differed significantly for groups of positive or negative molecular findings. Out of the eight parameters tested, RDW, MCHC and rectic were found to be significantly different between groups of positive and negative molecular analysis. Then, the RDW, MCHC and Retic were then anaylzed using ROC Curve to determine the cut-off values for positive molecular findings, respectively. The cut-off values for MCHC and Retic could be determined while cut-off values for RDW could not be determined as the area under the curve was less than 0.5. The cut-off values for MCHC was equal or greater than 34.15 g/dL while the cut-off value for Retic was equal or greater than 2.1%.